APPLICATION OF BOOTSTRAP METHOD ON ESTIMATION OF THE ERROR RATES IN DISCRIMINANT ANALYSIS - MANGKU, I W. (School of Data Science, Mathematics and Informatics, IPB University, 2004)
This paper is a survey study on applications of boot- strap methods for estimating the probability of misclassiﬁcations in two-groups discriminant analysis. Here we use the linear discrimi- nant function as classiﬁcation rule. Some comparative studies on the performances of the considered estimators are also discussed.